2019
DOI: 10.3390/ijerph16204027
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review and Conceptual Model of Social Participation and Mental Health among Refugees and Asylum Seekers

Abstract: Social participation plays a key role in the integration of refugees and asylum seekers into their host societies, and is also closely tied to the mental health of those populations. The aim of this scoping review was to study how the concept of social participation is described in empirical research, and how it is associated with mental health outcomes. Methods: In total, 64 studies were identified through searches in PubMed, PsycInfo, and Sociological Abstracts. These studies describe various forms of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 91 publications
2
29
0
Order By: Relevance
“…[16][17][18] The REFUGE-study approaches integration in agreement with the primary domains suggested by Ager and Strang, 19 which are: employment and labour market, school and education attainments, housing, and health and healthcare. Furthermore, and in line with suggestions by Castles et al 20 and Niemi et al, 21 we consider civic and social participation/social exclusion to be central indicators of refugees' access to and active involvement in important spheres of the host societies, and these markers thus indicate a central component of social capital. 22 Congruent with the domains of integration suggested by Ager and Strang, the study will use data from the Norwegian national registries in order to measure integration for consenting participants.…”
Section: Integrationsupporting
confidence: 89%
“…[16][17][18] The REFUGE-study approaches integration in agreement with the primary domains suggested by Ager and Strang, 19 which are: employment and labour market, school and education attainments, housing, and health and healthcare. Furthermore, and in line with suggestions by Castles et al 20 and Niemi et al, 21 we consider civic and social participation/social exclusion to be central indicators of refugees' access to and active involvement in important spheres of the host societies, and these markers thus indicate a central component of social capital. 22 Congruent with the domains of integration suggested by Ager and Strang, the study will use data from the Norwegian national registries in order to measure integration for consenting participants.…”
Section: Integrationsupporting
confidence: 89%
“…Consistent with the SEM methodology, the items in the three self-report scales on postmigratory stress, coping and well-being were treated as reflective indicators of underlying latent constructs [49]. Theory and prior studies on refugee populations guided the actual modeling of latent constructs [9,50], with modification indices consulted to improve fit when necessary. The overall aim was to establish theoretically grounded and well-fitted measurement models.…”
Section: Measurement Models For Sem Methodologymentioning
confidence: 99%
“…Unfortunately, there is less clarity on how to intervene on the profound effects of post-migratory stressors [ 20 ]. Evidently, the impact of post-migratory stressors can be partially reduced by practical changes, such as obtaining a job or increased proficiency in the host country language [ 21 ], as well as by policies enabling these factors [ 22 ]. This level of intervention, however, often requires policy change in host countries, and thus is usually beyond the influence of individual refugees and their helpers.…”
Section: Introductionmentioning
confidence: 99%